2016
DOI: 10.1111/acel.12514
|View full text |Cite
|
Sign up to set email alerts
|

mTORC 1 activation decreases autophagy in aging and idiopathic pulmonary fibrosis and contributes to apoptosis resistance in IPF fibroblasts

Abstract: SummaryIdiopathic pulmonary fibrosis (IPF) is a chronic, progressive, and usually lethal disease associated with aging. However, the molecular mechanisms of the aging process that contribute to the pathogenesis of IPF have not been elucidated. IPF is characterized by abundant foci of highly active fibroblasts and myofibroblasts resistant to apoptosis. Remarkably, the role of aging in the autophagy activity of lung fibroblasts and its relationship with apoptosis, as adaptive responses, has not been evaluated pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
126
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 151 publications
(132 citation statements)
references
References 47 publications
5
126
1
Order By: Relevance
“…Old and IPF lung fibroblasts have dysfunctional autophagy activity with increased LC3 puncta, p62 accumulation, and persistent activation of the mTOR pathway under starvation conditions. However, the activation of mTOR was further enhanced in IPF fibroblasts and associated with greater resistance to apoptosis (20). Altogether, these studies suggest that aberrant activation of mTOR and the resulting defective autophagy in aging IPF fibroblasts play a role in the development of lung fibrosis.…”
Section: Cellular Perturbations In the Ipf Lungmentioning
confidence: 80%
See 1 more Smart Citation
“…Old and IPF lung fibroblasts have dysfunctional autophagy activity with increased LC3 puncta, p62 accumulation, and persistent activation of the mTOR pathway under starvation conditions. However, the activation of mTOR was further enhanced in IPF fibroblasts and associated with greater resistance to apoptosis (20). Altogether, these studies suggest that aberrant activation of mTOR and the resulting defective autophagy in aging IPF fibroblasts play a role in the development of lung fibrosis.…”
Section: Cellular Perturbations In the Ipf Lungmentioning
confidence: 80%
“…Analyses of autophagy activity in aging murine lungs show markers of autophagy flux blockade (17,19). Most recently, we have shown that dysfunctional autophagy activity also occurs in aging lung fibroblasts from healthy humans (20). Senescence, mitochondrial dysfunction, and insufficient autophagy in the aging lung might have implications in maladaptive responses to stress.…”
mentioning
confidence: 91%
“…Based on their data, the authors suggested a protective feedback loop in which mTOR-dependent anti-inflammatory and antifibrotic regulation by SIRT1 fails in SSc, but can be functionally restored by elevating SIRT1 levels with resveratrol. Persistent activation of the mTOR pathway has also been shown in aged and IPF lung fibroblasts and linked to inhibition of autophagy, development of cellular senescence, and fibroblast resistance to apoptosis in pulmonary fibrosis [123, 124]. …”
Section: Sirtuins and Sclerodermamentioning
confidence: 99%
“…A notable feature of IPF is the presence of apoptosis-resistant lung fibroblasts. In a recent study, investigators found that normal aging promoted resistance to apoptosis through chronic basal activation of mTORC1 signaling and resultant suppression of autophagy (18). Fibroblasts from patients with IPF demonstrated a further increase in mTORC1 signaling.…”
Section: Mtor In Disease and Agingmentioning
confidence: 99%
“…mTOR and Lung Diseases mTOR has been studied in the context of two of the major lung diseases, idiopathic pulmonary fibrosis (IPF) and chronic obstructive pulmonary disease (COPD), with similar findings with regard to mTOR activity. Researchers in several studies have reported that basal levels of mTORC1 and mTORC2 signaling are elevated in either IPF fibroblasts or tissue biopsies (15)(16)(17)(18). A notable feature of IPF is the presence of apoptosis-resistant lung fibroblasts.…”
Section: Mtor In Disease and Agingmentioning
confidence: 99%